Industrial Electronics, 2002. ISIE 2002. Proceedings of the 2002 IEEE International Symposium On 2002
DOI: 10.1109/isie.2002.1026362
|View full text |Cite
|
Sign up to set email alerts
|

Engine idle speed control via maximal safe set computation in the crank-angle domain

Abstract: In this paper, the idle speed control problem is addressed via maximal safe set computation. A hybrid model of the engine in idle mode is used. The solution is based on the transformation of the continuous dynamics from the time-domain to the crank-angle domain and on the linearization and discretization of these dynamics. A ‡exible and portable algorithm in the discrete-time domain is proposed for the determination of the maximal safe set. Simulation results show the e¢ciency of the proposed approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Vd N mcyl(P m, N ) = 1 2 0 RT m TJintak e P m, (2) where N is engine speed, Vd is engine cylinders volume, TJintak e is volumetric efficiency, which can be considered as a function of manifold pressure and engine speed. It can be obtained as a MAP through experimental calibration.…”
Section: B Static Cylinder Air Inductionmentioning
confidence: 99%
“…Vd N mcyl(P m, N ) = 1 2 0 RT m TJintak e P m, (2) where N is engine speed, Vd is engine cylinders volume, TJintak e is volumetric efficiency, which can be considered as a function of manifold pressure and engine speed. It can be obtained as a MAP through experimental calibration.…”
Section: B Static Cylinder Air Inductionmentioning
confidence: 99%
“…In general, it is reported that the mean value engine model (MVEM) is sufficient for controller design [25,26]. But for some control algorithms it can be summed up from previous articles that it is hard to guarantee the objectivity when designing a speed controller for the reciprocating engine, because of the existence of these ignored characteristics in engine speed.…”
Section: Introductionmentioning
confidence: 99%
“…This is an important technical aspect in general, and in particular for our application, where there is no reason why sampling and switching caused by the piston reaching a dead center 2 should be synchronized. Further, it allows the extension of the results obtained in [Balluchi et al, 2002] where the error due to the lack of synchronization was not taken into account.…”
Section: Introductionmentioning
confidence: 99%